2017
DOI: 10.1159/000477463
|View full text |Cite
|
Sign up to set email alerts
|

Neck Management with Total Laryngectomy and Adjuvant Radiotherapy in Locally Advanced Larynx Cancer

Abstract: Background: The aim of this study was to determine whether patients with clinically node-negative (cN0) locally advanced squamous cell carcinoma (SCC) of the larynx who receive total laryngectomy (TL) benefit from elective neck dissection (END) before adjuvant postoperative radiotherapy (RT). Methods: A retrospective review of 36 patients who received TL and adjuvant postoperative RT for laryngeal SCC between 1988 and 2013 was carried out. Patients had either T3 (n = 7; 19%) or T4a (n = 29; 81%) primaries, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…In ENT departments, pharyngeal cancer is typically detected by ENT physicians at an advanced stage, when the patient is suffering hoarseness, swallowing pain, swallowing dysfunction, swollen neck lymph nodes, and/or dyspnea [13]. Because pharyngeal cancer can invade surrounding structures, such as the larynx, esophagus, or muscle, advanced disease requires invasive treatment; i.e., resection of the entire larynx, leading to loss of phonatory function [14].…”
Section: Discussionmentioning
confidence: 99%
“…In ENT departments, pharyngeal cancer is typically detected by ENT physicians at an advanced stage, when the patient is suffering hoarseness, swallowing pain, swallowing dysfunction, swollen neck lymph nodes, and/or dyspnea [13]. Because pharyngeal cancer can invade surrounding structures, such as the larynx, esophagus, or muscle, advanced disease requires invasive treatment; i.e., resection of the entire larynx, leading to loss of phonatory function [14].…”
Section: Discussionmentioning
confidence: 99%
“…This fact should not be underestimated and survival outcome should not be jeopardized when considering surgical refinement in terms of reducing the extent of dissection. In contrast, several previous retrospective studies showed no significant influence of elective neck dissection (END) on survival in advanced laryngeal cancers (Ketterer et al 2020;Shi et al 2019;Kennedy et al 2017;Djordjevic et al 2016;Canis et al 2012). For salvage TL cases, END is not generally recommended, because, although it reduces the rate of regional recurrence, it does not provide a survival benefit as stated in a recent meta-analysis (Davies-Husband et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Skora et al reported that adjuvant radiotherapy was given to 138 patients in the T3-4N0M0 stage, who underwent total laryngectomy and neck dissection; 34 patients experienced recurrence, and the five-year survival rate was 76% (22). Kennedy et al found a five-year local and regional control rate of 92% after adjuvant radiotherapy in their study consisting of 36 patients in the T3-T4aN0 stage (23). In the present research, adjuvant radiotherapy was applied to 20 patients with postoperative thyroid cartilage invasion, subglottic extension, and multiple or ECE metastatic lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%